2012
DOI: 10.1111/j.1748-1716.2011.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Reverse‐mode NCX current in mouse airway smooth muscle: Na+ and voltage dependence, contributions to Ca2+ influx and contraction, and altered expression in a model of allergen‐induced hyperresponsiveness

Abstract: Reverse-mode NCX activity leads to a physiologically relevant increase in [Ca(2+) ] even under control conditions, and this may be exaggerated in allergen-induced AHR and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…A role of NCX in mitochondria cannot be ruled out, since pharmacological modulation could cause changes in calcium flux from this pool of calcium (Svichar et al 1999). There is evidence that KB-R7943 can enhance Cadependent potassium conductance (Rahman et al 2012), which could contribute to modulation of neurite degeneration, although this occurs with higher concentrations of the drug, e.g., 30 M (Rahman et al 2012). While not excluding a contribution via these other routes, our data point to a role of reverse NCX, triggered by activity of sodium channels, as a contributor to calcium overload in G856D-expressing DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A role of NCX in mitochondria cannot be ruled out, since pharmacological modulation could cause changes in calcium flux from this pool of calcium (Svichar et al 1999). There is evidence that KB-R7943 can enhance Cadependent potassium conductance (Rahman et al 2012), which could contribute to modulation of neurite degeneration, although this occurs with higher concentrations of the drug, e.g., 30 M (Rahman et al 2012). While not excluding a contribution via these other routes, our data point to a role of reverse NCX, triggered by activity of sodium channels, as a contributor to calcium overload in G856D-expressing DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In ASM of humans without asthma, the reverse mode of NCX1 contributed to Ca 21 influx after histamine stimulation (46). Rahman and colleagues (47) recently suggested that the reverse mode of NCX1 altered Ca 21 mobility in mouse ASM. They also described increased gene expression of NCX1 in a chronic model with repeated HDM exposure that was not present in the acute model.…”
Section: Discussionmentioning
confidence: 99%
“…Since changes in membrane potential are known to affect ASM Ca 2ϩ handling (39) and cytosolic Cl Ϫ concentration ([Cl Ϫ ]) has been implicated in attenuating sarcoplasmic Ca 2ϩ flux (21,23), we questioned whether activation of ␣5-subunit-containing GABA A receptors on ASM could modulate intracellular calcium concentration ([Ca 2ϩ ] i ) and mediate relaxation of intact ASM.…”
mentioning
confidence: 99%